LIABILITY FOR CRIMES IS ESTABLISHED AGAINST JUSTICE SOME ISSUES OF THE DEVELOPMENT OF CRIMINAL LAW NORMS (Journal of Universal Science Research, 2023)
Тhis article analyzes the trends in the development of the norms of the established criminal legislation on responsibility for crimes against justice. In addition, opinions were expressed on certain aspects of the provisions of this law, as well as conclusions and recommendations were developed.